Perception of negative earnings persistence and value relevance: Evidence from Zimbabwe - Atanas Sixpence; Olufemi Patrick Adeyeye (Cogent Economics & Finance, 2018)
This paper investigates the impact of negative earnings persistence on the value relevance of earnings before interest and taxes (EBIT) and book values for 27 non-financial firms listed on the Zimbabwe Stock Exchange (ZSE). Negative earnings are perceived to be persistent where firms reported losses in at least 25% of the time over the eight-year study period. Two-step System GMM was used, with the average debt-equity ratio and net asset value per share being additional regression instruments. The regressions were primarily done on the ZSE full sample, and then on a profit-reporting firms' sample. The loss-reporting firms' sample was too small for meaningful regressions. It was found that when loss-firms were removed from the sample, value relevance of EBIT and book value declined. This means that investors are very meticulous with firms they perceive to be persistent loss-makers but tend to be complacent with profit-firms.
Keywords: C23; M49; 330; value relevance; negative earnings persistence; book value; EBIT; Zimbabwe